Iatrogenic perforation of esophagus successfully treated with Endoscopic Vacuum Therapy (EVT) - Loske, Gunnar; Schorsch, Tobias; Dahm, Christian; Martens, Eckhard; Müller, Christian (Endoscopy International Open, 2015)
Background and study aims: Endoscopic Vacuum Therapy (EVT) has been reported as a novel treatment option for esophageal leakage. We present our results in the treatment of iatrogenic perforation with EVT in a case series of 10 patients.Patients and methods: An open pore polyurethane drainage was placed either intracavitary through the perforation defect or intraluminal covering the defect zone. Application of vacuum suction with an electronic device (continuous negative pressure, –125 mmHg) resulted in defect closure and internal drainage.Results: Esophageal perforations were located from the cricopharyngeus (4/10) to the esophagogastric junction (2/10). EVT was feasible in all patients. Eight patients were treated with intraluminal EVT, one with intracavitary EVT, and one with both types of treatments. All perforations (100 %) were healed in within a median of (3 – 7) days. No stenosis occurred, no complications were observed, and no additional operative treatment was necessary.Conclusions: Our study suggests that intraluminal EVT will play an important role in endoscopic management of esophageal perforation.